A Study of the Reactions of 3‐Bromopropenals with Anilines for the Synthesis of α‐Bromo Enaminones. Issue 21 (7th September 2021) - Suresh, Sundaram; Bhimrao Patil, Prakash; Yu, Pao‐Hsing; Fang, Chia‐Chi; Weng, Yin‐Zhi; Kavala, Veerababurao; Yao, Ching‐Fa
Abstract: A one‐pot strategy for the synthesis of α ‐bromo enaminones is reported. The reactions proceed via the p ‐toluenesulfonic acid monohydrate (TsOH ⋅ H2 O) catalyzed reactions of 3‐bromopropenals with anilines in dimethyl sulfoxide (DMSO) and does not require an external brominating agent. The chemoselective 1, 2‐addition was accomplished by employing aniline with a sterically hindered electron‐withdrawing group attached at the ortho ‐position. In addition, the reactions involving other aniline derivatives as nucleophiles have resulted in minor yields of 1, 4‐addition product. The 3‐bromopropenals showed a diverse range of reactivities with aniline derivatives. Abstract :